2016
DOI: 10.2147/jpr.s105892
|View full text |Cite
|
Sign up to set email alerts
|

A review of chronic pain impact on patients, their social environment and the health care system

Abstract: Chronic pain (CP) seriously affects the patient’s daily activities and quality of life, but few studies on CP have considered its effects on the patient’s social and family environment. In this work, through a review of the literature, we assessed several aspects of how CP influences the patient’s daily activities and quality of life, as well as its repercussions in the workplace, and on the family and social environment. Finally, the consequences of pain on the health care system are discussed. On the basis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
561
1
30

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 709 publications
(601 citation statements)
references
References 76 publications
9
561
1
30
Order By: Relevance
“…Such negative associations also have been found in previous research 47. Our regression models accounted for 35%–70% of the total variance of QoL, indicating that pain intensity and depression play an important role in the variation of QoL.…”
Section: Discussionsupporting
confidence: 88%
“…Such negative associations also have been found in previous research 47. Our regression models accounted for 35%–70% of the total variance of QoL, indicating that pain intensity and depression play an important role in the variation of QoL.…”
Section: Discussionsupporting
confidence: 88%
“…Chronic pain is common, disabling, has limited effective treatment options and is costly to healthcare systems and society. 64 This challenging field is also currently immersed in one of the worst iatrogenic crises to date and is struggling to find new, non-opioid, therapeutic options. 65 …”
Section: An Illustrative Examplementioning
confidence: 99%
“…Research suggests that CWP is often unsuccessfully identified and managed within primary care and that consequently there is a tendency for overuse of healthcare appointments and thus health service utilisation [11, 12]. …”
Section: Introductionmentioning
confidence: 99%